Particulate Matter Emission during the Combustion of Bio-oil Based Biofuels under Conditions Pertinent to Stationary Applications - Feng, Chao (Curtin University, 2018)
This thesis investigates the particulate matter emission from the combustion of various bio-oil-based biofuels, including bio-oil, bio-oil/biochar slurry, and crude-glycerol-containing biofuel mixtures, through a lab-scaled drop-tube furnace system at 1400 °C under various conditions pertinent to stationary applications. The emission characteristics and mechanisms were discussed and benchmarked against conventional solid fuels. The related influences from different combustion conditions and synergies between different fuel components were also studied. The corresponding trace element emission was also reported.